Rancang Bangun Sistem Informasi Money Receipts and Expenditures Pada PT.HAP - Ilamsyah Ilamsyah; Feri Noviana; Amarulloh Amarulloh (UNIVERSITAS RAHARJA, 2021)
This research paper is motivated by the importance of designing an information system that can provide a report on Money Receipts and Expenditures in a company. PT.HAP (Hydroraya Adhi Perkasa) is a construction company that runs large projects, currently the Money Receipts and Expenditures system uses a system that is not fully computerized, where the recording process still uses a form and the admin staff must input it back into Microsoft Excel. Problems occur when making reports, due to mishandling, it makes it difficult for the Money Receipts and Expenditures report to be made quickly, so that it has an impact on company losses due to delays in reports and data that are not well controlled. Due to these problems, a Web-based information system was created with the aim of making it easier for the Admin Staff in making reports that were fast, accurate, effective and efficient. To design an information system, several methods are used, among others; analysis method using PIECES, system modeling method using UML, programming language using PHP, Framework using Code Igniter, making the database using MySQL-Server. The final results of this study are in the form of a Web-based Money Receipts and Expenditures Information System to be implemented at PT.HAP as an alternative solution to the problems faced.